Psychological and Pedagogical Conditions of Complex Understanding of Healthy Lifestyle of the Future Teachers - Kokoilo, Yulia Aleksandrovna (Psychological Prospects Journal, 2012)
This article studies the problem of maintaining health and a healthy lifestyle (HLS) by the students of Pedagogical University. A new definition of health, which contains the maximum semantic content is formulated. The understanding level of the future teachers healthy lifestyle is investigated, the necessity for the formation of their complex understanding of healthy lifestyles is grounded and the system of psychological and pedagogical conditions directed at achieving it is proposed.